The Effectiveness Of Grammarly Application On Writing Descriptive Text Tenth Grade SMA Negeri 1 Lau Baleng - Cikep Kosasih Galingging; Kammer Tuahman Sipayung; Harpen Silitonga; Sanggam Pardede (Departement of Mathematics Education, 2023)
This thesis about The Effect of Grammarly Application on Student’s writing descriptive text in the tenth Grade of SMA Negeri 1 Lau Baleng. The objective of the study is intended to find out the effect of Grammarly Application on students’ writing skill in SMA Negeri 1 Lau Baleng. The research design used in this study was experimental quantitative design which true experimental. The population of this study is the Grade X students of SMA Negeri 1 Lau Baleng with six classes, and there are MIPA 1,2,& 3 IPS 1,2 & 3. The sample of the research is two classes ( MIPA 1 &2 ), that selected by using random sampling. The sample is divided into two groups; the first group is 22 students as the experimental group. The second group is 22 students as the control group. The instrument used for collecting the data was test in the form essay writing with choose one of 5 topic that has been prepare. The tests are divided into two; pre-test and post-test. The data was analyzed by using t-test formula in order to see whether the Grammarly application affects students’ writing skill. The result of the analysis shows that t-test (3,53), it is higher than the t-table (2,021) with the level of significant (0,05) and the degree of freedom (df) (42). The result of the analysis shows that the alternative hypothesis (Ha) of the study is accepted and the null hypothesis (Ho) is rejected because t-test > t-table =3,53 > 2,021. Grammarly application is very helpful for students in learning English because there are many tools and the exercises so challenging so that the students not bored in learning English. It is concluded that theGrammarly application recommended in the students’ writing descriptive text at tenth grade of Senior High School because it is above of KKM (75).